Analisis Faktor Determinan Yang Mempengaruhi Pembiayaan Perbankan Syariah Dengan Pertumbuhan Ekonomi Sebagai Variabel Moderating - Luki Tias Sari; Amrizal Amrizal (Indonesian Journal of Economics Application (IJEA), 2020)
This study aims to determine the effect of inflation, non-perfoming financing, and third party funds on financing with economic growth as a moderating variable in Islamic banking. The independent variable consists of Inflation, Non-performing Financing and Third Party Funds. The dependent variable used in Financing. The moderating variable used is economic growth. This study uses a purposive sampling technique using 48 samples taken from Sharia Banking 2015 - 2018. The test results show that the Inflation variable has a positive and significant effect on Islamic banking financing. Non-performing financing variable has a positive but not significant effect on Islamic banking financing. Variable third party funds have a positive and significant impact on Islamic banking financing. Economic growth as a moderating variable weakens the relationship between inflation and Islamic banking financing. Economic growth as a moderating variable weakens the relationship between NPF and Islamic banking financing. Economic growth strengthens the relationship between DPK and Islamic banking financing. Simultaneously the independent variables consisting of Inflation, Non-performing Financing and Third Party Funds can influence or influence simultaneously on Sharia Banking Financing.